2022
DOI: 10.3390/ijerph19053079
|View full text |Cite
|
Sign up to set email alerts
|

The Workplace and Psychosocial Experiences of Australian Senior Doctors during the COVID-19 Pandemic: A Qualitative Study

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has had significant mental health impacts among healthcare workers (HCWs), related to resource scarcity, risky work environments, and poor supports. Understanding the unique challenges experienced by senior doctors and identifying strategies for support will assist doctors facing such crises into the future. A cross-sectional, national, online survey was conducted during the second wave of the Australian COVID-19 pandemic. Inductive content analysis was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Numerous senior physicians reported stress, dissatisfaction, and upheavals in their duties and responsibilities at home and the office, resulting in a significant pressure on their work-life balance and burnout. Participants also expressed the feeling of neglect for their safety on the job, and many felt devalued by their employer and the government, with unsatisfactory leadership at all levels [44] , [45] . Younger age, a higher level of education, a higher degree, and several social factors, including decreased social support, having a relative or friend diagnosed with COVID-19, low family, and colleague readiness to cope with COVID-19, increased the perceived threat of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous senior physicians reported stress, dissatisfaction, and upheavals in their duties and responsibilities at home and the office, resulting in a significant pressure on their work-life balance and burnout. Participants also expressed the feeling of neglect for their safety on the job, and many felt devalued by their employer and the government, with unsatisfactory leadership at all levels [44] , [45] . Younger age, a higher level of education, a higher degree, and several social factors, including decreased social support, having a relative or friend diagnosed with COVID-19, low family, and colleague readiness to cope with COVID-19, increased the perceived threat of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…There was significant uncertainty regarding the risk of occupational transmission of SARS‐CoV‐2, limited availability of personal protective equipment, social isolation and restrictions on the provision of health care. Through subsequent waves of infection, frontline health care workers in hospital and aged care settings were particularly impacted, with reported concerns including excessive workload, insufficient rest and fatigue, SARS‐CoV‐2 transmission risk, social isolation, financial loss and pervasive uncertainty 43,44 . Smallwood et al.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a positive association between overall job satisfaction and AG among professionals has been observed in therapists and nurses working with trauma victims in Poland (Ogińska-Bulik et al, 2021). Regarding satisfaction with workplace-related arrangements, a qualitative study on Australian senior doctors indicated that unsafe working environment, insufficient quality personal protective equipment, and relative guidelines could contribute to their well-being (Tran et al, 2022). However, studies on how satisfaction with other aspects of work-related resources (e.g., wage, workload, and the way hospital policies putting into practice) might contribute to nurses’ AG are limited.…”
Section: Healthcare Workers’ Mental Health In the Context Of Covid-19mentioning
confidence: 99%